Investigation of the depth impact of the ironing process using SEM images and CAD system - Ficzere, Péter; László, Noémi (Design of Machines and Structures, 2023)
The adoption of additive manufacturing within the automotive sector is progressively growing, primarily attributed to the technology’s speed, relative ease of use, and its capability to manufacture components with intricate geometries that are beyond the reach of traditional methods. This holds especially true for enhanced or structured plastic parts. A variety of instrumental, analytical, and image analysis techniques are accessible for both qualitative and quantitative assessment of surface structures. This article outlines the potential of utilizing scanning electron microscopy (SEM) and CAD for image analysis in this context.